Arbitrating disputes in the Republic of North Macedonia - Deskoski Toni; Dokovski Vangel (Strani pravni život)
This paper deals with the arbitration framework in North Macedonia, presenting the dualistic approach to domestic and international arbitration as provided by the national Law on International Commercial Arbitration (hereafter: LICA) and the national Code of Civil Procedure (hereafter: CPA). The LICA is based on the 1985 UNCITRAL Model Law on International Commercial Arbitration, which provides a legal framework for resolving disputes with an international element, allowing the parties the freedom to choose between ad hoc or institutional arbitration. Contrary to that, domestic disputes are exclusively reserved for institutional arbitration. Furthermore, this paper addresses subjective and objective arbitrability, and analyzes the arbitrability of corporate, employment and defamation disputes. The procedural aspects of arbitration, particularly the role of institutional arbitration in North Macedonia and the governing rules for arbitration procedures, are also exploited. The issue of recognition and enforcement of foreign arbitral awards in North Macedonia is also analyzed in this paper. Recent judicial practices have demonstrated deviation from the Private International Law Act (hereafter: PIL Act), notably turning ex parte proceedings into contradictory ones, which undermines the PIL Act. A case involving the refusal to recognize a Partial ICC Award from Poland and later setting aside the award illustrates these issues, as the court failed to properly apply the LICA and the PIL Act. This deviation is also analyzed in the paper.